A Comparative Analysis of Anglo-Dutch Approaches to 'Cyber Policing': Checks and Balances Fit for Purpose?. (October 2020) - Brants, Chrisje; Jackson, Adam; Wilson, Tim J
This article examines two contrasting approaches to the governance of police investigations for ensuring that cybercrime-policing is lawful and ethical. The Netherlands has a national police force working under the direction of an equally centralised prosecution service according to specific laws on the use of special powers of surveillance, with evidence tested judicially when added incrementally to the case file. Theoretically, the process of adapting to the novel features of cybercrime policing should be much easier than within the much more fragmented policing structure in England and Wales, where unreliable evidence is challengeable only at the trial stage and the laws governing police action are equally fragmented. The Dutch police, however, have not found it easy to adapt concepts of covert policing developed in the 1990's to their on-line investigative activities, despite the existence of comparatively detailed guidance and case law for undercover policing in the 'real' world. In the UK, the police seem unsure which requirements and concepts actually apply to their different on-line-investigations. More generally, it is concluded that legal comparisons of the kind undertaken in this article can identify general bottlenecks and barriers to adapting to the cyber environment, but such analysis cannot identify best practices that are readily transferable from one country to another. Legal transplants are a potentially hazardous undertaking because any practices and policies that work successfully will do so because they are necessarily compliant with the underlying systemic legal-cultural factors that make each legal system unique. Indeed, we make no attempt to identify best practices, other than to remark that the centralised nature of Dutch policing seems to afford some advantage, although, for historical and legal-cultural reasons, centralisation is unlikely to be an option for the UK police forces